The Influence of Competence, Cooperation and Organizational Climate on Employee Performance With Work Motivation as a Mediation Variable (Study on the Food and Agriculture Office Clump of Merauke Regency) - Rimbayana, Terisius Andreas Kasman; Erari, Anita; Aisyah, Siti (Technium Social Sciences Journal, 2022)
The purpose of the study was to determine the effect of competence, cooperation, and organizational climate on employee performance mediated by work motivation (a study in the food and agriculture office clump work unit in Merauke Regency). The research uses a quantitative research approach. The sampling technique used purposive sampling method. The research sample as many as 117 employees were selected from Civil Servants (PNS) as structural or implementing officials, not as Field Agricultural Extension Officers (PPL) or civil servants who were not on duty in the unit. The data comes from the answers to the questionnaire according to the employee’s perception. The results of the questionnaire were tabulated and analyzed using Structural Equation Modeling (SEM) using the SmartPLS application. The results of the analysis prove that competence has a significant effect on performance, competence has an effect on work motivation, and motivation mediates the influence of competence on employee performance. Cooperation has no effect on performance, but has an effect on motivation and work motivation mediates the effect of cooperation on employee performance. Organizational climate does not affect employee performance but organizational climate affects work motivation and work motivation mediates the relationship between organizational climate and employee performance. Motivation has a significant effect on performance. The results of the study have implications for competence and motivation that need to be improved in order to improve employee performance. Motivation variable affects performance by 48.6% and competence affects performance by 28.2%. Increasing work motivation can be done by increasing cooperation and organizational climate.